2017
DOI: 10.1038/s41598-017-09536-z
|View full text |Cite
|
Sign up to set email alerts
|

Altered Lipid Metabolism in Recovered SARS Patients Twelve Years after Infection

Abstract: Severe acute respiratory syndrome-coronavirus (SARS-CoV) and SARS-like coronavirus are a potential threat to global health. However, reviews of the long-term effects of clinical treatments in SARS patients are lacking. Here a total of 25 recovered SARS patients were recruited 12 years after infection. Clinical questionnaire responses and examination findings indicated that the patients had experienced various diseases, including lung susceptibility to infections, tumors, cardiovascular disorders, and abnormal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
355
0
25

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(387 citation statements)
references
References 26 publications
7
355
0
25
Order By: Relevance
“…However, some important messages can be gleaned from previous experiences with SARS, caused by SARS-CoV which shares considerable similarity with SARS-CoV-2. It was reported that among patients who had recovered from SARS, 68% continued to have abnormalities of lipid metabolism at 12-years follow-up; CV abnormalities were present in 40% and altered glucose metabolism in 60% [12]. Similar findings have also been reported in patients recovering from other respiratory tract infections [13].…”
Section: Potential Long-term Consequencessupporting
confidence: 54%
See 1 more Smart Citation
“…However, some important messages can be gleaned from previous experiences with SARS, caused by SARS-CoV which shares considerable similarity with SARS-CoV-2. It was reported that among patients who had recovered from SARS, 68% continued to have abnormalities of lipid metabolism at 12-years follow-up; CV abnormalities were present in 40% and altered glucose metabolism in 60% [12]. Similar findings have also been reported in patients recovering from other respiratory tract infections [13].…”
Section: Potential Long-term Consequencessupporting
confidence: 54%
“…Although data is lacking, the prevalence of various CV Both tachyarrhythmia and bradyarrhythmia can occur but exact nature not described Potential long-term consequences Too early to assess Too early to ascertain for coronavirus disease 2019. However, patients recovering from a similar earlier illness-Severe Acute Respiratory Syndrome-continued to have long-term abnormalities of lipid and glucose metabolism and of cardiovascular homeostasis [12] * Acute cardiac injury is a non-specific term with significant overlap with other cardiovascular manifestations; however, it is listed here because of how reporting has been done in most of the studies on coronavirus disease 2019.…”
Section: Role Of Underling CV Comorbiditiesmentioning
confidence: 99%
“…Metabolomics analysis revealed that lipid metabolism was dysregulated in patients with a history of SARS-CoV infection. In these patients, the serum concentrations of free fatty acids, lysophosphatidylcholine, lysophosphatidylethanolamine and phosphatidylglycerol were significantly increased compared with individuals without a history of SARS-CoV infection 7 . However, the mechanisms by which SARS-CoV infection leads to disorders of lipid and glucose metabolism are still uncertain.…”
Section: Chronic Cardiovascular Damagementioning
confidence: 78%
“…A 12-year follow-up survey of 25 patients who recovered from SARS-CoV infection found that 68% had hyperlipidaemia, 44% had cardiovascular system abnormalities and 60% had glucose metabolism disorders 7 . Metabolomics analysis revealed that lipid metabolism was dysregulated in patients with a history of SARS-CoV infection.…”
Section: Chronic Cardiovascular Damagementioning
confidence: 99%
“…Overall, there is increasing awareness of the involvement of host genetic factors in infectious diseases. Coronavirus infections may induce long-term abnormalities in lipid and glucose metabolism, with clear adverse implications for FH patients, and, additionally, chronic Chlamydia pneumoniae infection is associated with an increased risk of coronary artery disease in patients with FH [3,4]. An important finding is the association between cytomegalovirus antibodies and atherosclerosis, which in the Atherosclerosis Risk in Communities Study was observed in individuals with high levels of lipoprotein(a) and fibrinogen [5].…”
mentioning
confidence: 99%